2002
DOI: 10.1152/ajpendo.00136.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of free fatty acids on hepatic glycogenolysis and gluconeogenesis in conscious dogs

Abstract: .-The aim of this study was to determine the effect of high levels of free fatty acids (FFA) and/or hyperglycemia on hepatic glycogenolysis and gluconeogenesis. Intralipid was infused peripherally in 18-h-fasted conscious dogs maintained on a pancreatic clamp in the presence (FFA ϩ HG) or absence (FFA ϩ EuG) of hyperglycemia. In the control studies, Intralipid was not infused, and euglycemia (EuG) or hyperglycemia (HG) was maintained. Insulin and glucagon were clamped at basal levels in all four groups. The ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 38 publications
5
45
0
Order By: Relevance
“…This finding is in agreement with the report of Gastaldelli et al (9) and the well-established stimulatory effect of FFAs on gluconeogenesis (9,28,29). Boden et al (30) have shown that an increase in plasma FFAs produced by means of an intralipid heparin infusion impairs insulin-induced suppression of glycogenolysis in nondiabetic subjects.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is in agreement with the report of Gastaldelli et al (9) and the well-established stimulatory effect of FFAs on gluconeogenesis (9,28,29). Boden et al (30) have shown that an increase in plasma FFAs produced by means of an intralipid heparin infusion impairs insulin-induced suppression of glycogenolysis in nondiabetic subjects.…”
Section: Discussionsupporting
confidence: 91%
“…Boden et al (30) have shown that an increase in plasma FFAs produced by means of an intralipid heparin infusion impairs insulin-induced suppression of glycogenolysis in nondiabetic subjects. In contrast, Chu et al (28) have reported that elevated FFAs in the presence of hyperglycemia enhance, rather than impair, suppression of glycogenolysis. The observation that plasma FFAs were positively correlated with glycogenolysis during the clamp in the current study suggests that endogenous FFAs also modulate the ability of insulin to suppress glycogenolysis in obese nondiabetic and diabetic humans.…”
Section: Discussionmentioning
confidence: 87%
“…To our knowledge, metformin-induced enhancement of insulin signaling in the liver has not previously been identified in any in vivo model of insulin resistance. Previous studies of lipid-induced insulin resistance in a few species have demonstrated that accelerated gluconeogenesis is primarily responsible for the increased HGO observed (4,7,9,20,21); however, not all studies have detected a net effect on HGO, because a concurrent effect of lipid to suppress glycogenolysis has been observed (4,9). In this study, we quantified the expression of two key gluconeogenic enzymes (FBP and PEPCK) in the liver after lipid infusion but did not detect differences in expression of either enzyme as a result of lipid infusion or metformin.…”
Section: Discussionmentioning
confidence: 96%
“…Hyperlipidemia is an important component of this syndrome; in particular, elevation of circulating free fatty acid (FFA) concentrations has been associated with insulin resistance in many clinical studies (2,3). Furthermore, artificial elevation of systemic FFA in normal humans or animals by means of triacylglycerol-heparin infusion (4 -10) or increasing dietary fat content (11,12) results in insulin resistance, usually involving a substantial impairment in the ability of insulin to suppress hepatic glucose output (HGO) (4,7,9). Several groups have identified changes in expression or activation of molecules linked to the insulinsignaling cascade as a result of increased supply of FFAs to the liver.…”
mentioning
confidence: 99%
“…The former slowed increasing glucose disposal, and the latter slowed suppression of FFA, hence slowing the suppression of glucose output. There is still debate regarding what precise fraction of suppression of glucose output is secondary to suppression of FFA (85). However, there is consensus that FFA suppression accounts for at least part of the reduction in gluconeogenesis and glycogenolysis that accompanies nutrient intake.…”
Section: Branch #3: the Role Of Ffas In Insulin Action And Glucose Homentioning
confidence: 99%